Performance evaluation of stable weight based on demand routing in MANET - Oon, Chong Hsi; Abdullah, Azizol (Science Publication, 2009)
Problem statement: A MANET is an autonomous collection of mobile users that communicate over relatively bandwidth constrained wireless links. Since the nodes are mobile, the network topology may change rapidly and unpredictably over time. Approach: A Stable Weight-based On demand Routing Protocol (SWORP) that uses the weight-based route strategy to select a stable route was created by Wang. But SWORP only evaluated in a limited setting of simulation, more simulation parameter have to test with SWORP to evaluate how far this protocol can go on. In this project, SWORP was implemented in simulation environment with two other routing protocols, AODV and DSR. Results: These three protocols were implemented in Network Simulator 2 (NS2) and the performance was compare with performance metrics, end-to-end delay, number of packet drop and packet delivery ratio. Conclusion: As expected, SWORP had outperformed AODV and DSR in the overall routing performance.